JOB BURNOUT AND FLEXIBLE WORKING ARRANGEMENT ASSOCIATIONS ON EMPLOYEE WELLBEING WITH PERCEIVED ORGANIZATIONAL SUPPORT AS MEDIATOR: A STUDY DURING PANDEMIC - Amri, Muhammad Miftahul; Maharani, Anita; Hidayah, Zainur (Jurnal Aplikasi Manajemen, 2022)
This study investigated the association between job burnout and flexible working arrangement on employee wellbeing with perceived organizational support as a mediator. The study is conducted on 127 employees of an Indonesian telecommunication company. The data is obtained between November 2021 and January 2022 using an anonymous online survey. We employ the partial least squares-structural equation modeling (PLS-SEM) method to analyze the data. The result finds that the level of employees' job burnout is in a low category. In addition, the employees have a positive view of the FWA implementation. As for POS, the employees perceive adequate POS. The findings also reveal that the employees have a sufficiently good well-being level. Furthermore, the statistical analysis shows that the POS variable is influenced by JB and FWA variables; and has a positive and significant effect on the EW variable. In addition, JB and FWA variables have a positive and significant effect on EW, either directly or mediated by the POS variable. Note that this research was conducted at the branch of the telecommunication company at a province level. Hence, the result might not represent the employees throughout Indonesia. Moreover, the variables of interest were limited to job burnout, FWA, POS, and employee wellbeing, making a relatively limited number of operational variables. Finally, the research findings contribute to the HRM to improve the organization through employee wellbeing management.